TO STUDY THE IN VITRO INHIBITION OF BLOOD PLATELET AGGREGATION BY ISOLATED COMPOUNDS FROM CLAUSENA DENTATA (WILLD.) ROEM. - ANNAMALAI MADURAM; RAJU KAMARAJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objectives of the study were to study the antiplatelet aggregation activity of compounds isolated from extracts of Clausena dentata. Clausena (Rutaceae) is a genus of about 23 species of unarmed trees and shrubs. The stem bark of C. dentata is used in veterinary medicine for the treatment of wounds and sprains. Even though C. dentata has a lot of potential medical uses, the study of pharmacological properties is very scarce. Methods: The plant C. dentata was collected from Kadagaman, near Tiruvannamalai, Tamil Nadu, India, and authenticated by Centre for Advanced Study in Botany, University of Madras, Chennai. The dry powder of stem bark was extracted with hexane, chloroform, and methanol. The extracts were subjected to qualitative phytochemical screening and column chromatography. Four compounds were isolated. All the isolated compounds were subjected to adenosine diphosphate (ADP)-induced platelet aggregation and compared with aspirin. Results: The isolated compounds from C. dentata and standard aspirin showed significant antiplatelet activity against ADP-induced platelet aggregation. Conclusion: The compounds, 3-(1,1-dimethylallyl)xanthyletin, dentatin, nordentatin, and carbazole showed significant antiplatelet aggregation activity. Among the compounds, nordentatin showed more activity of antiplatelet aggregation.